Determinants of innovativeness in regional SMES - Fernández-Jardón, Carlos Maria (Revista de Administração da UFSM, 2012)
The innovativeness is a core competence to innovate and therefore enhancing competitiveness, especially in small and medium enterprises (SMEs). This capability is constrained by internal and external factors. This article discusses how the company combines these factors to improve innovativeness. First, the company generates a core competence called human resource management and technology from internal intellectual capital. Furthermore, the company organizes another core competence called resource management and territorial relations from tangible resources associated with intellectual capital territory and fruit of the relationship with the environment. Using partial least squares techniques applied to a sample of small and medium enterprises in a region in northwest Spain is shown that both factors influence innovativeness. This study helps to define what the factors that enhance innovativeness are and how those factors associated company, indicating the process of building core competencies to improve their innovativeness. Consequently, for thought suggests to develop policies to support business innovation.